The design and construction of sheet-piled cofferdams - Williams, B. P (CIRIA special publication, 1993)
A guide to help the engineer understand the basic principles of the design of cofferdams, this book brings together information which is likely to be needed for the successful design and construction of a cofferdam up to 10 metres deep in steel sheet piling.